Erythrocyte indices and serum ferritin in newborns - Nunes,Maria de Fatima Pussick (2010)
Hematological values for newborn babies differ depending on the gestational age and intrauterine growth. However, information in published studies about hematological values for cord blood according to weight-for-gestational-age categories is limited and inconsistent, especially regarding small-for-gestational-age (SGA) newborns. With the aim of describing hematological values for umbilical cord blood, we conducted a cross-sectional study in two government maternity hospitals in Salvador, Brazil. Eighty-eight healthy, term, appropriate-for-gestational-age (AGA), 23 term, small-for-gestational-age (SGA), and 13 preterm, AGA newborns were studied. Means and standard deviation, and maximum and minimum values were used to describe the level of hemoglobin (Hb), red blood cells (RBC), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), red cell distribution width (RDW) and serum ferritin. The highest values of RBC, Hb, HCT and serum ferritin were recorded for term SGA newborns and the lowest values were recorded for preterm AGA newborns. Term AGA newborns had intermediate values for all these parameters. In this study we observed the highest hematological values in SGA newborns. Because, these infants are at the highest risk of iron deficiency, the use of more detailed screening tests for iron deficiency in these newborns at birth, using a combination of biomarkers, should be considered.